A Review of Concept of Sharia Marketing, Customer Satisfaction, Trust, and Loyalty - Setiawan, Afif Mahardika; Yulianto, Edy; Kusumawati, Andriani (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
The aim of this study is to provide a literature review around the relationship between sharia marketing and customer satisfaction, trust, and loyalty. A company that applies sharia marketing needs to consider the services being offered in order to maintain customer satisfaction, because this becomes the contact point that allows trust and loyalty on the services given by a company. Various kinds of hypotheses can be created from this theory, this conceptual study is intended to review the relationship between variables from 13 research that resulting in emergent debates and differences that lead to different studies from the proposed hypotheses. Each of these conceptual is the result of previous studies that still need to be developed and substantiated in order to be able to verify studies involving these variables further scientifically.